Imperative Speech Acts Among Junior High School Students: A Study at SMP Negeri 1 Parigi - Nur Alifta; Yunidar Yunidar; Arum Pujining Tyas; Syamsuddin Syamsuddin; Juniati Juniati (Global Education Journal, 2026)
This study discusses the form and function of imperative speech actions between students of SMP Negeri 1 Parigi. The purpose of this study is to describe the form and function of imperative speech actions between students of SMP Negeri 1 Parigi. The method carried out in this study is qualitative research. The data collection carried out is by observation, recording, watching and recording. The subject of this study is speech between students of SMP Negeri 1 Parigi. The data analysis techniques carried out in this study include three stages, namely data reduction, data presentation, and conclusion drawn. The results of the study showed that the form of imperative speech between SMP Negeri 1 Parigi students consisted of the form of command, the form of request, the form of giving permission, the form of invitation, and the form of command. The function of imperative speech actions found in the use of regional languages and Indonesian is unified in speech between students to build social structure and cooperation in the school environment. The form of imperative speech between students is as follows: Command has three data, Request has four data, Permission grant has three data, Invitation has four data, Command has two data. Meanwhile, the functions obtained are as follows: Command Imperative Function as many as three data, Request Imperative Function as many as four data, Imperative Permission Function as many as three data, Invitation Imperative Function as many as four data, and Imperative Command Function as many as two data.